Causes and Consequences of Civil Strife : Micro-Level Evidence from Uganda - Deininger, Klaus (World Bank, Washington, DC, 2014)
To bridge the gap between case studies and highly aggregate cross-country analyses of civil unrest, the author uses data from Uganda to explore determinants of civil strife (as contrasted to theft and physical violence) at the community level, as well as the potentially differential impact of these variables on investment and nonagricultural enterprise formation at the household level. He finds that distance from infrastructure (a proxy for scarcity of economic opportunities and government investment), asset inequality (social tension), the presence of cash crops (expropriable wealth), and lower levels of human capital (ability to take advantage of opportunities in the "regular" economy) all increase the propensity for civil strife. Furthermore, civil strife, in marked contrast to violence and theft, reduces investment and nonagricultural enterprise start-ups.